2021
DOI: 10.3389/fcell.2021.658101
|View full text |Cite
|
Sign up to set email alerts
|

hTERT Promotes CRC Proliferation and Migration by Recruiting YBX1 to Increase NRF2 Expression

Abstract: High human telomerase reverse transcriptase (hTERT) expression is related to severe Colorectal Cancer (CRC) progression and negatively related to CRC patient survival. Previous studies have revealed that hTERT can reduce cancer cellular reactive oxygen species (ROS) levels and accelerate cancer progression; however, the mechanism remains poorly understood. NFE2-related factor 2 (NRF2) is a molecule that plays a significant role in regulating cellular ROS homeostasis, but whether there is a correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…One study reported that YBX1, the “readers” of m 5 C modification, activated NF signaling pathway in CRC ( 38 ). Moreover, the transcription factor YBX1 enhanced the expression of NRF2 by binding to its promoter region, promoting the proliferation of CRC cells ( 39 ). YBX1 also served as a mediator of signaling in the EGFR-RAS-MAPK axis ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that YBX1, the “readers” of m 5 C modification, activated NF signaling pathway in CRC ( 38 ). Moreover, the transcription factor YBX1 enhanced the expression of NRF2 by binding to its promoter region, promoting the proliferation of CRC cells ( 39 ). YBX1 also served as a mediator of signaling in the EGFR-RAS-MAPK axis ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hTERT G4-targeting small molecule (RG1603), or pharmacological inhibitor of hTERT (costunolide) and siRNA-mediated depletion of hTERT expression resulted in inhibition of NRF2 and HO-1 expression in glioblastoma and prostate cancer [86,87]. Interestingly, hTERT was found to be primarily upregulated NRF2 by increasing NRF2 promoter activity rather than by regulating NRF2 mRNA or protein stability in colon cancer cells [88]. Considering our results, which revealed that CA increased both NRF2, telomerase, and proteasome activity, we aimed to identify the underlying mechanism in the next step.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hTERT G4-targeting small molecule (RG1603), or pharmacological inhibitor of hTERT (costunolide) and siRNA-mediated depletion of hTERT expression resulted in inhibition of Nrf-2 and HO-1 expression in glioblastoma and prostate cancer (Ahmad et al, 2016; Song et al, 2019). Interestingly, hTERT was found to be primarily upregulated Nrf-2 by increasing Nrf-2 promoter activity rather than by regulating Nrf-2 mRNA or protein stability in colon cancer cells (Gong et al, 2021). Considering our results, which revealed that CA increased both Nrf-2, telomerase, and proteasome activity, we aimed to identify the underlying mechanism in the next step.…”
Section: Discussionmentioning
confidence: 99%